Evolving Trends in Financial Stressor Research Across the Asian Continent: A Systematic Review and Bibliometric Analysis Using VOSviewer - Elsya, Venny; Layyina, Ulya (JURNAL BISNIS STRATEGI, 2025)
Objectives: This study examines financial stressor research trends in Asia from 2015 to 2024, aiming to identify thematic priorities, collaboration networks, and existing gaps, thereby offering evidence for policy development and future research directions.Methods: Following PRISMA guidelines, a total of 1,149 peer-reviewed articles from Scopus, Science Direct, and Google Scholar were examined. VOSviewer (version 1.6.19) was chosen for its ability to visualize extensive datasets via co-authorship networks, keyword co-occurrence maps, and bibliographic coupling. The software’s clustering algorithms revealed research hotspots and collaboration trends, applying keyword thresholds of 15 citations for co-citation analysis and 8 occurrences for thematic mapping.Results: Post-2020, publications surged by 78.3%, driven by COVID-19 impacts. China (26.8%), India (17.2%), and South Korea (9.7%) dominated output, while cross-country collaborations (e.g., China-U.S.: 47 papers) highlighted global linkages. VOSviewer revealed five top keywords from those articles: financial stress (21.3% of studies), financial stability (18.7%), economic policy uncertainty (17.5%), financial literacy emerged as a critical mitigator appearing in 18.7% by 2023 studies and food insecurity on rural populations (6.2% ) and cross-country comparisons (7.8%).Conclusion: Mapping financial stressors across the Asian continent using VOSviewer's strong analytical tools can highlight key stressors and gaps to be resolved. These research findings could be beneficial to inform the financial policy of the state or government, including addressing the lack of financial literacy, which can serve as a proximal buffer against financial stress.